Impact of computerization on corporate performance - Han, Chun Kwong; Mohamed, Mohd Zain (1986)
The impact of computerization on corporate financial performance in a sample of petroleum copanies is evaluated. A computerization index that measures the extent and sophistication of computerization is computed. This composite index incorporates the number of installations, software staff, shifts of operations, years of computer usage, the size of CPU, hardware costs, ;ocation of EDP activity, level of management, and costs/benefit analysis of computerization projects. Corporate financial performance is measured in terms of six strategic ratios, namely, profit/total assests, profit/sales, sales/total assets, gross margin/sales, profit growth rate and sales growth rate. The analysis revealed that financial performance is positively correlated with the degree of computerization.